2019
DOI: 10.1016/j.foodres.2018.12.012
|View full text |Cite
|
Sign up to set email alerts
|

A cross-cultural perspective on feeling good in the context of foods and beverages

Abstract: The aim of the present research was to explore consumers' conceptualization of feeling good in relation to food and beverages from a cross-cultural perspective. Participants from 14 countries across 5 continents and covering 10 languages (N=8,325) responded to an online survey including word association and free listing tasks related to feeling good in the context of food and beverages. Results were analyzed using inductive coding: a list of main codes was generated in English for each of the tasks, after whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…From the 327 respondents, 3924 terms, related to the three stimuli presented (Figure 1), were elicited with a mean of 3.7 words per stimulus and consumer. Terms were grouped into 586 valid codes, assembled into 112 categories, and these categories in 10 dimensions based on previous studies [54,66]. Only 23 categories, grouped in eight dimensions, were mentioned by at least 10% of the consumers [63], and were included in the analysis ( Table 5).…”
Section: Wa Taskmentioning
confidence: 99%
See 2 more Smart Citations
“…From the 327 respondents, 3924 terms, related to the three stimuli presented (Figure 1), were elicited with a mean of 3.7 words per stimulus and consumer. Terms were grouped into 586 valid codes, assembled into 112 categories, and these categories in 10 dimensions based on previous studies [54,66]. Only 23 categories, grouped in eight dimensions, were mentioned by at least 10% of the consumers [63], and were included in the analysis ( Table 5).…”
Section: Wa Taskmentioning
confidence: 99%
“…WA is used in sensory science to understand how consumers perceive novel or abstract concepts [58]. This mental categorisation tool has been studied to develop new products [52,53,[56][57][58][59][60][61], to evaluate new packaging [55,62], and undefined concepts [58,59,66,87]. These studies concluded that WA provided interesting and valuable information for gathering consumer perceptions [104].…”
Section: Wa Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that the Danish consumers experience PIFP as more related to the body's physical needs, whereas the Chinese consumers experience PIFP as more connected to the body's 'mental' needs. Previous research has also reported differences in the values associated to food and eating between Western countries and China [5,6], e.g., results have pointed towards cultural differences in the way we associate for instance wellbeing and 'feeling good'. Sulmont-Rossé et al (2019) report cross-cultural perspectives on 'feeling good' in the context of food using qualitative approaches.…”
Section: Cross-cultural Differences In Drivers Of Post-ingestive Foodmentioning
confidence: 93%
“…Considering the globalization and emergent food markets, where foods are exported beyond national borders, we need to take into consideration cultural aspects when seeking to understand human eating behaviors on the respective markets [2]. Consequently, cross-cultural research has become increasingly more pertinent within Sensory and Consumer Science [3,4], and several studies suggest that cultural differences exist in the way we perceive food, in our associations with specific foods, and also within food-related concepts [5][6][7][8][9][10][11]. The contribution and importance of cross-cultural research studies thus bring new perspectives in the domain of Sensory and Consumer Science, and it contributes to the development and understanding of various food concepts.…”
Section: Introductionmentioning
confidence: 99%